Effective communication in criminal justice - Grubb, Robert E.; Hemby, K. Virginia (SAGE Publications, Inc., 2019)
"Authors Robert E. Grubb and K. Virginia Hemby teach students how to be both effective writers and communicators--essential skills for anyone interested in criminal justice. Going beyond report writing, this book helps readers become more confident presenters and digital communicators while encouraging students to adapt their communication styles to meet the needs of diverse populations. Students will not only improve their communication and writing skills but also gain specific strategies for succeeding in careers related to policing, courts, corrections, and private security."--Back cover.